REGIONAL GRAVITY STUDY OF PERAK, MALAYSIA USING SATELLITE ACQUIRED DATA - bin Kamaruzzaman, M.Y. (Asian Research Publishing Network, 2020)
Gravity method is one of the methods in geophysics that involves measuring the earth's gravitational field at specific locations on the surface of the earth. It is used to determine the subsurface properties according to anomalies which indicate density variations. The main objective of this study is to determine subsurface geological properties in Perak, Malaysia using satellite acquired corrected gravity anomaly data obtained from Earth Gravitational Model 2008 (EGM2008). With the aid of Oasis Montaj, a software by Geosoft, the data from 296225 station points are used to produce Bouguer Anomaly map. By comparing the Bouguer Anomaly map produced with the geological map of Perak, three zones can be determined from the anomaly value which are high, intermediate and low. High anomaly zone (> 10 mGal) can be seen on Quaternary rocks due to the influence of high density oceanic crust. Intermediate anomaly zone (-10 to 10 mGal) can be seen on Palaeozoic rock formation. In this zone, low value can be seen on rocks closer to granite formation and higher towards oceanic crust. Low anomaly zone (<10 mGal) can be seen on areas with granitic body due to isostatic compensation. From the GYM-Sys filter of the Oasis Montaj software, two estimated two dimensional gravity model is produced from two lines (A-B) and (B-C) drawn on the Bouguer Anomaly map. These models were deduced based on the formation information provided by past researches. Â© 2020